Black Samson: the untold story of an American icon - Junior, Nyasha (Oxford University Press, 2020)
Introduction : What we talk about when we talk about Samson -- Black Samson in the Temple of Liberty -- Black Samson of Brandywine -- Samson and the making of American martyrs -- Black Samson and labor movements -- The Samson complex -- But some of us are strong believers in the Samson myth -- Visual representations of Black Samson.